Teaching About and For Social Justice - Joanne Robertson; Awneet Sivia (Language and Literacy: A Canadian Educational e-journal)
Teaching for social justice is an explicit goal of most teacher education programs. However, this mandate has been criticized by scholars who claim that social justice is an undertheorized and vague concept that is often disconnected from methods courses that focus on content-specific pedagogies. This study seeks to address this disconnect by exploring how an Equity Literature Circles (ELC) framework within a literacy methods course can enhance teacher candidates’ (TCs’) understanding of the relationship between literacy instruction, diversity, and social justice. Drawing on the perceptions of ten TCs enrolled in a teacher education program in western Canada, data for the study was generated from classroom artifacts, an individual survey, and a focus group interview. Upon analysis of the data, the findings suggest that an ELC framework is an effective instructional strategy for enhancing TCs’ understanding of intersecting aspects of diversity, equity-focused literacy instruction, and teaching about and for social justice.